2006
DOI: 10.1073/pnas.0507105103
|View full text |Cite|
|
Sign up to set email alerts
|

Depth sectioning with the aberration-corrected scanning transmission electron microscope

Abstract: The ability to correct the aberrations of the probe-forming lens in the scanning transmission electron microscope provides not only a significant improvement in transverse resolution but in addition brings depth resolution at the nanometer scale. Aberration correction therefore opens up the possibility of 3D imaging by optical sectioning. Here we develop a definition for the depth resolution for scanning transmission electron microscope depth sectioning and present initial results from this method. Objects suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
162
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 236 publications
(164 citation statements)
references
References 22 publications
2
162
0
Order By: Relevance
“…It has been pointed out that the focal depth of an aberration-corrected microscope in the STEM mode can be reduced by increasing the convergence angle of the probe (Borisevich et al 2006) or by using a confocal geometry (Frigo et al 2002;Nellist et al 2006). This makes it possible to retrieve detailed structural information from defects contained within the crystal volume (Lupini et al in press).…”
Section: (A) Detection Of Buried Defectsmentioning
confidence: 99%
“…It has been pointed out that the focal depth of an aberration-corrected microscope in the STEM mode can be reduced by increasing the convergence angle of the probe (Borisevich et al 2006) or by using a confocal geometry (Frigo et al 2002;Nellist et al 2006). This makes it possible to retrieve detailed structural information from defects contained within the crystal volume (Lupini et al in press).…”
Section: (A) Detection Of Buried Defectsmentioning
confidence: 99%
“…Optical sectioning has been demonstrated in previous work for single Hf atoms in SiO 2 (van Benthem et al 2005) and for small Pt and Au nanoparticles in a TiO 2 powder (Borisevich et al 2006). The positions of single atoms were located in three dimensions by van Benthem et al (2005) with an error of less than a nanometre, while Borisevich et al (2006) showed that the reconstructed shapes of large particles are elongated along the optic axis. In this paper, we present results from experimental STEM optical sectioning of samples containing Pt and Au nanoparticles of varying size.…”
Section: Introductionmentioning
confidence: 99%
“…been demonstrated previously [21,22]. In a non-confocal geometry, however, this approach can only be used for high-resolution imaging as the 3D transfer function for incoherent STEM imaging shows a missing cone which results in significant elongation in 3D images of laterally extended objects [23].…”
Section: Using This Reduced Depth Of Focus To Retrieve 3d Informationmentioning
confidence: 99%